The Effect of Using Learning Models Project Based Learning (PjBL) on Science Learning Outcomes - Azizah; Nurul Annisa; Zulnuraini; Sisriawan Lapasere (Tadulako Social Science and Humaniora Journal, 2022)
This research aims to determine the influence of the Project Learning (PjBL) learning model on the Science Learning Outcomes of Class V Students at SDN Inpres 1 Birobuli. The subjects in this research were 49 class V students of SDN Inpres 1 Birobuli. This type of research is quantitative research. The sample in this study was class Va as the experimental class and Vb as the control class. The instrument used is a multiple choice test which has been tested for validity and reliability. Data analysis used prerequisite tests, namely the normality test and homogeneity test as well as hypothesis testing using paired sample t-test which was analyzed using IBM SPSS Statistics 25. Based on the research results, it showed a significance value (2-tailed) of 0.000 < alpha value of 0.05. Because of the sig value. 0.000 < 0.05 then accepts the Ha hypothesis and rejects Ho. So it can be concluded that there is an influence of the Project Based Learning (PjBL) learning model in improving the science learning outcomes of class V students at SDN Inpres 1 Birobuli.